Beyond Corporate Social Media Platforms: The Epistemic Promises and Perils of Alternative Social Media. - Frost-Arnold, Karen (Topoi: An International Review of Philosophy, 2024)
In recent years, we have witnessed increased interest in alternatives to the dominant corporate social media sites, such as Facebook, Twitter (now X), and TikTok. Tired of disinformation, harassment, privacy violations, and the general degradation of platforms, users and technologists have looked for non-corporate alternatives. Not-for-profit social media platforms emerging from free/libre and open-source software (FLOSS) communities based on non-centralized infrastructure have emerged as promising alternatives. For applied epistemology of the internet, these alternative social media platforms present an opportunity to study different ways of producing knowledge together online. This paper evaluates the epistemic potential for such alternative, non-corporate social media. I present an epistemological framework for analyzing the epistemic promises and perils of alternative social media. Then I apply this framework to the case of Mastodon, a federated, open-source microblogging platform. Mastodon's structure and culture of openness present opportunities to avoid many of the epistemic perils of biased and untrustworthy large corporate platforms. However, Mastodon's risks include techno-elitism, white ignorance, and isolated, epistemically toxic communities.